Penggunaan Alat Peraga Dalam Pembelajaran Tematik Untuk Meningkatkan Prestasi Belajar Tema Diri Sendiri Pada Siswa Kelas II SD Negeri 024 Rambah Samo Tahun Pelajaran 2016/2017 - Zulmaidah Zulmaidah (STKIP Rokania Pasir Pangaraian, 2018)
This research is a research action (action research). Subjects in this study amounted to 28 people consisting of 11 men and 17 women who are students of second grade academic year 2016/2017. The focus of this research is learning with the use of teaching aids in thematic learning to improve student achievement of second grade students of SD Negeri 024 Rambah Samo. The use of props has been proven to improve student's learning achievement from the grade average of 68,57 to 92,14 in cycle II